CircKEAP1 Suppresses the Progression of Lung Adenocarcinoma via the miR-141-3p/KEAP1/NRF2 Axis - Wang, Yanbo; Ren, Fenghai; Sun, Dawei; Liu, Jing; Liu, BenKun; He, YunLong; Pang, Sainan; Shi, BoWen; Zhou, FuCheng; Yao, Lei; Lang, YaoGuo; Xu, ShiDong; et al. (Frontiers in Oncology, 2021)
Background Lung cancer is the leading cause of death from cancer, and lung adenocarcinoma (LUAD) is the most common form. Despite the great advances that has been made in the diagnosis and treatment for LUAD, the pathogenesis of LUAD remains unclear. In this study, we aimed to identify the function of circKEAP1 derived from the exon of KEAP1 in LUAD. Methods The expression profiles of circRNAs in LUAD tissues and adjacent non-tumor tissues were analyzed by Agilent Arraystar Human CircRNA microarray. The levels and prognostic values of circKEAP1 in tissues and cancer cell lines were determined by quantitative real-time PCR (qRT-PCR). Subsequently, the effects of circKEAP1 on tumor growth were investigated by functional experiments in vitro and in vivo. Mechanistically, the dual luciferase reporter assay, RNA pull-down, and RNA immunoprecipitation experiments were performed to confirm the interaction between circKEAP1 and miR-141-3p in LUAD. Results We found circKEAP1 was significantly downregulated in LUAD tissues and repressed tumor growth both in vitro and in vivo. Mechanistically, circKEAP1 competitively binds to miR-141-3p and relive miR-141-3p repression for its host gene, which activated the KEAP1/NRF2 signal pathway, and finally suppresses the tumor progress. Our findings suggest that circKEAP1 inhibits LUAD progression through circKEAP1/miR-141-3p/KEAP1 axis and it may serve as a novel method for the treatment of LUAD.